THE STRATEGIC ROLES OF HUMAN CAPITAL, LEARNING AND INNOVATION CAPABILITIES TO INDONESIAN PHARMACEUTICAL COMPANY PERFORMANCE - Sampurno Sampurno (Faculty of Pharmacy, Universitas Gadjah Mada)
Pharmaceutical industry is strongly konwledge-based and research-intensive with knowledge product as the competitive advantages determinant.In the pharmaceutical industry, human capital is strategic assets as the main pilar of organizational competence in creating values to satisfy its customer’s need. Human capital is the key for competitiveness and the key for making innovations. In this contex, knowledge mastery is very crusial to pharmaceutical company. A company can have competitive advantage if they know how to extend, disseminate, and exploate knowledge internally and know how to protect it from being imitated by its competitors. For doing this, individual as well as collective learning in the company is needed in order to integrate different streams of various technologies, which at the same time strengthen its core competence.. Learning will also strengthen its absorbtive capacity, which in turn enables the company to absorb knowledge form external sources to be combined with internal capabilities have been possessed by the company. Within pharmaceutical industry, innovation capability, eitherin terms of innovation process or products, play signifikan important role in creating competitive advantage. Without innovation capability, a pharmaceutical company will be stagnant because it will not be able to respond the demands of hightly dynamic market. Learning capabilitycloselyrelates to innovation outcome. Orgaizatuional learning process has very strong relationship with organizational perfornmance. This research tested the strategic roles of human capital, learning and innovation capabilities to Indonesian pharmaceutical companies. This research was carried out through field study, while the data process and analysis was done with Structural Eqution Modeling (SEM) using Lisrel 8.7 program. This research found that pharmaceutical companies with veru strong human capital, and superior learning and innovation capacities had excellent organizational performance with sustainable competitiveness. These three variables were found to be critical determinants of competitive advantage of Indonesian pharmaceutical companies. Keywords: Human capital. Learning, innovation, competitive advantage and company performance